Problem Cankarjeve Lepe Vide - Poniž, Denis (Jezik in slovstvo, 2005)
The last play by Ivan Cankar, Lepa Vida, written in 1912, is one of those literary works that gained an extremely modest reception response from Slovene literary historians; there are also few clear definitions of what this play means for Cankar's playwriting and his entire literary art. The paper is an introductory chapter of an extensive study researching historical fate and response, and also the present reception of this play, which broke ties with Cankar's social and aesthetically enagaged literature of the time, and opened up towards a different understanding of the world and people. Through many question of principle, offered by Cankar´s play, the article points out its framework of method and meaning and the problems that came to light in the above-mentioned study.
Keywords: Cankar, Ivan: Lepa Vida; literarne študije